Phytochemicals as Potential Chemopreventive and Chemotherapeutic Agents for Emerging Human Papillomavirus–Driven Head and Neck Cancer: Current Evidence and Future Prospects - Aggarwal, Nikita; Yadav, Joni; Chhakara, Suhail; Janjua, Divya; Tripathi, Tanya; Chaudhary, Apoorva; Chhokar, Arun; Thakur, Kulbhushan; Singh, Tejveer; Bharti, Alok Chandra (Frontiers in Pharmacology, 2021)
Head and neck cancer (HNC) usually arises from squamous cells of upper aero-digestive tract that line the mucosal surface in the head and neck region. In India, HNC is common cancer in males and sixth most common cancer globally. Conventionally, HNC attributes to the use of alcohol or chewing tobacco. Over the past four decades, portions of human papillomavirus (HPV) positive HNC are increasing at an alarming rate. Identification based on the etiological factors and molecular signatures demonstrates that these neoplastic lesions belong to a distinct category that differ in pathological characteristics and therapeutic response. Slow development in HNC therapeutics has resulted in a low 5-year survival rate in the last two decades. Interestingly, HPV-positive HNC has shown better outcome following conservative treatments and immunotherapies. This raises demand to have a pre-therapy assessment of HPV status to decide the treatment strategy. Moreover, there is no HPV specific treatment for HPV-positive HNC. Accumulating evidence suggests that phytochemicals are promising leads against HNC and show potential as adjuvants to chemo-radiotherapy in HNC. However, only a few of these phytochemicals target HPV. Aim of the present article is to collate data on various leading phytochemicals that have shown promising results in the prevention and treatment of HNC in general and HPV-driven HNC. The review explores the possibility of using these leads against HPV positive tumors as some of the signalling pathways are common. The review also addresses various challenges in the field that prevent their use in clinical settings.